A high performance piezoelectric–triboelectric hybrid energy harvester by synergistic design. (28th July 2022) - Khatua, Dipak Kumar; Kim, Sang-Jae
Abstract : Generation of electricity from naturally abandoned mechanical vibrations is of utmost importance in the modern era of the internet of things. Abstract : Generation of electricity from naturally abandoned mechanical vibrations is of utmost importance in the modern era of the internet of things. This strategy is highly beneficial to drive low power electronic devices and useful to numerous sensor applications, which include stress/strain sensing, tissue regeneration, environmental remediation, etc. Piezoelectrics are the preferred choice as mechanical energy harvesters and for related applications. Ferroelectric ceramics with the general formula ABO3 are the primary choice of piezoelectrics for these applications. Such systems show a high piezoelectric coefficient ( d 33 ) owing to collaborative interactions of the inherent polarization vectors of the crystal lattices. Here, we have invoked the idea of grain size-assisted polarization enhancement for improved piezoelectric energy harvesting (PEH) performance of BaTiO3 in the form of a polymer/ceramic composite. This composite also exhibits improved triboelectric energy harvesting (TEH) performance owing to the high dielectric constant of the ceramics. Grain size has a dramatic effect on the dielectric constant along with influencing d 33 . Here we demonstrate how the performance of a hybrid device relying on the PEH and TEH processes can be improved by grain size variation. Our approach shows a new way to improve the performance of hybrid mechanical energy harvesting devices.